Pengaruh Pengetahuan Dan Sikap Terhadap Minat Berwirausaha Pada Mahasiswa Program Kewirausahaan Lintas Prodi - Muhamad Ali; Rohaeniyah Zein; Nirwana Nirwana (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
The aims of this study were to: analyze the influence of entrepreneurial knowledge on entrepreneurial interest in cross-study entrepreneurship program students, analyze the effect of knowladge entrepreneurship for attitude in cross-study entrepreneurship program students,  and analyze the influence of attitudes on entrepreneurial interest in cross-study entrepreneurship program students. This research was a quantitative approach with descriptive research type. The subjects of this study were 101 students who had finished taking entrepreneurship courses across study programs. Techniques of collection data were carried out by interviewing and distributing questionnaires. The analyzed of data was used quantitative descriptive analysis techniques. The tool of analiticall used was SEM (structural equation modeling) with AMOSS software programs. The results of this study were indicated: knowledge of entrepreneurship has a positive effect on interest in entrepreneurship in cross-study entrepreneurship program students, those were indicated by the value of the standardized regression weight coefficient obtained by 0.521 and the C.R value of 4.331 with a probability value of 0.000 (p 0.05), knowledge of entrepreneurship has a positive effect on attitude in cross-study entrepreneurship program students, those were indicated by the value of the standardized regression weight coefficient obtained by 0,464 and the C.R value of 3,834 with a probability value of 0.000 (p 0.05), and attitudes has a positive effect on interest in entrepreneurship in cross-study entrepreneurship program students. Those were indicated by the value of the standardized regression weight coefficient obtained by 0.333 and the C.R value of 2.517 with a probability value of 0.012 (p 0.05)